1994
DOI: 10.2134/jeq1994.00472425002300010007x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Soil and Cropping Systems in the Development of Regional Water Quality Policies

Abstract: Targeting certain soils and cropping systems may be necessary in consideration of regional water quality protection policies. However, little information is available relating soils and cropping practices to regional water quality problems. This study evaluates crop yield and NO3‐N movement to surface and groundwater on four soils and nine principal cropping systems in the High Plains region of Oklahoma. The cropping systems involve wheat (Triticum aestivum L.), grain sorghum [Sorghum bicolor (L.) Moench], and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Poiani and Bedford (1995) recently presented a cursory review of GE-based NPS pollution models emphasizing surface applications. Numerous hydrologic-water quality models of runoff and soil erosion have been used with a GIS to determine surface sources of NPS pollutants from watersheds (Pelletier, 1985;Potter et al, 1986;Oslin et al, 1988;Sivertun et al, 1988;DeRoo et al, 1989DeRoo et al, , 1992Rudra et al, 1991;Bhaskar et al, 1992;Drayton et al, 1992;Joao & Walsh, 1992;Tim et al, 1992;Walker et al, 1992;Wolfe, 1992;He et al, 1993;Heidtke & Auer, 1993;Levine et al, 1993;Mitchell et al, 1993;Warwick & Haness, 1994) agricultural areas (Hopkins & Clausen, 1985;Gilliland & Baxter-Potter, 1987;Hession & Shanholtz, 1988Panuska & Moore, 1991;Hamlett et al, 1992;Lee & White, 1992;Geleta et al, 1994;Tim & Jolly, 1994) and urban areas (Smith & Brilly, 1992;Smith, 1993;Ventura & Kim, 1993). In addition, several groundwater models have been coupled to a GIS to simulate water flow and/or NPS pol-lutants in aquifers (Kernodle & Philip, 1989;Baker & Panciera, 1990;Hinaman, 1993;Roaza et al, 1993;El-Kadi et al, 1994;Darling & Hubbard, 1994).…”
Section: Gis-based Models For Nps Pollution Estimationmentioning
confidence: 99%
“…Poiani and Bedford (1995) recently presented a cursory review of GE-based NPS pollution models emphasizing surface applications. Numerous hydrologic-water quality models of runoff and soil erosion have been used with a GIS to determine surface sources of NPS pollutants from watersheds (Pelletier, 1985;Potter et al, 1986;Oslin et al, 1988;Sivertun et al, 1988;DeRoo et al, 1989DeRoo et al, , 1992Rudra et al, 1991;Bhaskar et al, 1992;Drayton et al, 1992;Joao & Walsh, 1992;Tim et al, 1992;Walker et al, 1992;Wolfe, 1992;He et al, 1993;Heidtke & Auer, 1993;Levine et al, 1993;Mitchell et al, 1993;Warwick & Haness, 1994) agricultural areas (Hopkins & Clausen, 1985;Gilliland & Baxter-Potter, 1987;Hession & Shanholtz, 1988Panuska & Moore, 1991;Hamlett et al, 1992;Lee & White, 1992;Geleta et al, 1994;Tim & Jolly, 1994) and urban areas (Smith & Brilly, 1992;Smith, 1993;Ventura & Kim, 1993). In addition, several groundwater models have been coupled to a GIS to simulate water flow and/or NPS pol-lutants in aquifers (Kernodle & Philip, 1989;Baker & Panciera, 1990;Hinaman, 1993;Roaza et al, 1993;El-Kadi et al, 1994;Darling & Hubbard, 1994).…”
Section: Gis-based Models For Nps Pollution Estimationmentioning
confidence: 99%
“…Higher nitrogen concentration in the leaves of tomato plants grown under drip irrigation was reported by Badr and Abou El-Yazid (2007). Geleta et al (1994) compared drip and flood irrigation and concluded that drip irrigation resulted in lower NO 3 -N loss. Nutrient transport from the soil solution to the root surface takes place by two simultaneous processes: convection in water flow and diffusion (Junk 1996).…”
Section: Total Nitrogen (N) Concentration Of Leaf and Stemmentioning
confidence: 99%
“…Because its original focus was erosion-related, EPIC can simulate decade-scale or longer intervals. These features have suited EPIC to a broad range of applications, including plant nutrition studies (Cole et al, 1987;Dautrebande et al, 1999); national and international assessments of agroecological change impact (Brown and Rosenberg, 1999;Brown et al, 2000;Bernardos et al, 2001), including the High Plains Aquifer (Easterling III et al, 1993); irrigation planning and water use (Bryant et al, 1992;Ellis et al, 1993;Evers et al, 1998;Guerra et al, 2005); and regional studies (Geleta et al, 1994;Cabelguenne et al, 1995;Fortin and Moon, 2000).…”
Section: The Epic Modelmentioning
confidence: 99%